Undervaluation of directors in the board hierarchy: Impact on turnover of directors (and CEOs) in newly public firms. (12th January 2018) - Garg, Sam; Li, Qiang (John); Shaw, Jason D.
Abstract : Research summary : We examine the consequences of the formalization of the board leadership structure at IPO for board‐level turnover. We introduce the concept of director undervaluation. It indicates the degree to which a director's qualifications based on normatively accepted criteria for board leadership are not duly reflected in his/her appointments to the board chair and committee chair positions. We find that the higher the average undervaluation of directors on the board ("board undervaluation"), the greater the turnover levels of undervalued directors. This effect is stronger when board interaction frequency is higher. We contribute to the behavioral perspective on corporate governance by introducing justice‐based legitimacy as a key normative institution, and by providing a novel predictor of aggregate turnover of directors (as well as the firm's CEO). Managerial summary : Why do outside directors exit the board? We offer a novel answer to this question in the context of newly public firms. We suggest that when directors are passed over for the board chair and committee chair positions despite having higher qualifications than their peers, they have been "undervalued, " and a negative board climate is likely to develop. We find that the higher the average undervaluation of directors on the board, the higher the turnover levels of these undervalued directors. More frequent board meetings exacerbate these turnover levels. Further, these turnover effects are not restricted to undervalued directors—even the CEO is more likely to exit. This study demonstrates the critical importance of developing a legitimate and fair board leadership structure.